Measurement of carpal bones: Comp arlson between sonographic method And standard radiographic method in Normal children in HUSM Kubang Kerlan Kelantan - Nasriah, Ahmad (2007)
Measurement of carpal bones: Comparison between sonographic method and standard radiographic method in normal children in HUSM Kubang Kerian Kelantan. Objectives: 1. To determine the presence of carpal bones by ultrasound and to measure the diameter of the visualized carpal bones, comparing with gold standard left hand radiograph. 2. To determine the difference in measurement of the carpal bones by ultrasound and radiograph. 3. To determine the difference in bone age assessment between 2 observers. Methods and Materials: Twenty four (24) normal children were evaluated for bone age from April 2005 until October 2006. Each child was examined by standard left hand radiograph and ultrasound examination of the left wrist. Sonographic examination was performed on the carpal bones to see its presence and to measure the transverse diameter. Bone age was evaluated by comparing the left hand radiograph with the standards of Greulich and Pyle atlas. Diameter of carpal bones measured by ultrasonography and radiograph was compared, the mean difference and agreement between 2 methods were calculated. Mean difference between bone age and chronological age, and intcrobserver difference w.er.e also calculated. Results: Mean bone age and chronological age was 8.38 :I: 3.45 years and 8.79 :I: 2.73 y.ears respectively. In .all cases, the carpal bones which w.ere seen on radiograph w.er.e detected by ultrasound. Cartilaginous ossification centers were detected by ultrasound but not demonstrated on radiograph in 3 subjects. Good correlation was found between ultrasound and radiograph (ICC of 0.907) in the measur.em.entof ~arpal bones. A high degree of agreement was found between 2 observers in the assessment of bone age (ICC of 0.988). The mean difference between chronological age and bone age was 0.40:1: 1.304 y.ears.and was not significant. CODclusion: Sonographie examination was able to detect cartilaginous ossification centers at .the wrist. Ev.en though there was a .good correlationbetw.een the 2 .m.ethods,thediameter of earpal bone alone cannot be used to determine bone age. Ultrasonographie evaluation is more valuable if combined with radiography of the hand.